Process Evaluation of an Application-Based Salt Reduction Intervention in School Children and Their Families (AppSalt) in China: A Mixed-Methods Study - Sun, Yuewen; Li, Yuan; He, Feng J.; Liu, Hueiming; Sun, Jingwen; Luo, Rong; Guo, Chunlei; Zhang, Puhong (Frontiers in Public Health, 2022)
Background: Salt reduction is a cost-effective, and rather challenging public health strategy for controlling chronic diseases. The AppSalt program is a school-based multi-component mobile health (mhealth) salt reduction program designed to tackle the high salt intake in China. This mixed-methods process evaluation was conducted to investigate the implementation of this program across sites, identify factors associated with the implementation, and collect evidence to optimize the intervention design for future scale-up. Methods: Mixed methods were used sequentially to collect data regarding five process evaluation dimensions: fidelity, dose delivered, dose received, reach, and context. Quantitative data were collected during the intervention process. Participation rate of intervention activities was calculated and compared across cities. The quantitative data was used for the selection of representative intervention participants for the qualitative interviews. Qualitative data were collected in face-to-face semi-structured interviews with purposively selected students (n=33), adult family members (n=33), teachers (n=9), heads of schools (n=9), key informants from local health and education departments (n=8). Thematic analysis technique was applied to analyze the interview transcripts using NVivo. The qualitative data were triangulated with the quantitative data during the interpretation phase. Results: The total number of families recruited for the intervention was 1124. The overall retention rate of the AppSalt program was 97%. The intervention was implemented to a high level of fidelity against the protocol. About 80% of intervention participants completed all the app-based salt reduction courses, with a significant difference across the three cities (Shijiazhuang: 95%; Luzhou: 73%; Yueyang: 64%). The smartphone app in this program was perceived as a feasible and engaging health education tool by most intervention participants and key stakeholders. Through the interviews with participants and key stakeholders, we identified some barriers to implementing this program at primary schools, including the left-behind children who usually live with their grandparents and have limited access to smartphones; perceived adverse effects of smartphones on children (e.g. eyesight damage); and overlooked health education curriculum at Chinese primary schools. Conclusion: This process evaluation demonstrated the feasibility and acceptability of using smartphone applications delivered through the education system to engage families in China to reduce excessive salt intake.